Plasma membrane H+-ATPase Pma1 regulates growth and virulence in Penicillium digitatum from citrus fruits involving iron homeostasis - Xinyue Lin; Huilin Kang; Shuzhen Yang; Gang Fan; Litao Peng; Hanyu Mu; Yanli Wang (Food Microbiology, 2026)

The multicopper ferroxidase Pdfet3 is essential for reductive iron assimilation, redox homeostasis, and virulence in Penicillium digitatum - Xinyue Lin; Shuzhen Yang; Hanyu Mu; Gang Fan; Litao Peng; Yanli Wang (Physiological and Molecular Plant Pathology, 2026)

Variations in source-originated health risks of soil heavy metals in an open-pit mining area, northern China from 2014 to 2023 - Yamei Shao; Weibo Ma; Yicong Chen; Yujuan Lv; Nan Wang; Jie Lin; Yanli Lv; Haidong Li (Journal of Environmental Sciences, 2026)

Whole-genome sequencing and metagenomic analyses provide genomic insights into tannin and saponin degradation regulated by lactic acid bacteria in anaerobic fermentation of paper mulberry - Ningwei Wang; Yunlei Sun; Yiying Shen; Mingxin Wu; Yanli Lin; Xuekai Wang; Kuikui Ni; Fuyu Yang (Food Bioscience, 2026)

Highly synergistic degradation of fluoroquinolones driven by redox dual channel mechanism in Fe(Ⅲ)-mediated thermally activated persulfate system - Lingzhi Shen; Yongpeng Zhang; Yuxing Xian; Zihong Xu; Zihao Guo; Yixun Zheng; Yue Yang; Zili Lin; Kun Yao; Zheng Hu; Yanli Wang; Zhenjun Xiao; et al. (Journal of Hazardous Materials, 2026)

Deciphering the regulation effect of glucans with various molecular weight on wheat starch entanglement behavior: From microstructure to gel rheological and textural properties - Lecheng Li; Mengyun Yue; Yanli Wang; Jianwei Zhao; Qianzhu Lin; Chao Qiu; Long Chen; Hangyan Ji; Zhengyu Jin (Food Research International, 2026)

Overlooked spectral matching-Enabled sulfoxide wastewater valorization and in situ pollutant elimination - Lingzhi Shen; Yue Yang; Yixun Zheng; Mengyang Niu; Zhiqing Lin; Zihong Xu; Yongpeng Zhang; Shan Yao; Yanli Wang; Kun Zhao; Zhenjun Xiao; Zili Lin; et al. (Journal of Cleaner Production, 2026)

Revealing performance and environmental thresholds of mangrove nature-based solutions: A nonlinear blue carbon response framework from coastal Hainan - Kaiyue Wang; Penghua Qiu; Dezhi Wang; Xinqing Zou; Meihuijuan Jiang; Tingting Si; Zhihang Wang; Yi Lin; Yanli Yang; Siang Wan; Yang Li (Journal of Environmental Management, 2026)

Recent advances in exopolysaccharides from lactic acid bacteria: Acquisition, characterization, bioactivities, and applications - Yanli Li; Wenye Zhang; Xiangmin Pan; Yonglan Xiao; Lin Liu; Fan Ding; Guangjian Li; Liqing Zhao (Food Bioscience, 2026)

Antifungal efficacy and fumigation potential of octanal and (E)-2-octenal against Aspergillus flavus in stored peanut seeds - Xuelian Zhu; Yuqi Yang; Tzuhan Lin; Weibin Ma; Yanli Xie (Food Control, 2026)

Impact of the Surface Roughness of Artificial Oyster Reefs on the Biofouling and Flow Characteristics Based on 3D Scanning Method - Yenan Mao; Shimeng Sun; Mingchen Lin; Hui Liang; Yanli Tang; Xinxin Wang (Journal of Marine Science and Engineering, 2026)
The complex surface architecture of natural oyster reefs is widely considered to promote biological attachment, yet the underlying mechanisms and the relevance to the design of artificial reefs are not fully understood. Here, we combined field experiments, 3D surface characterization, and numerical modelling to quantify how reef-like roughness regulates biofouling development and near-wall flow around artificial substrates. Surface morphological characteristics of natural oyster reefs were first obtained by 3D scanning and used to fabricate concrete panels with simulated rough textures, while traditional smooth concrete panels served as controls. The two types of panels were simultaneously deployed in the target sea area for a hanging-panel experiment. Samples were collected after 3, 6, 9, and 12 months to track changes in biofouling communities. At each sampling time, the panel surfaces were quantified by canopy roughness (RC), surface heterogeneity (σ), and fractal dimension (D), and these metrics were integrated into numerical simulations combined to resolve the flow field, turbulence kinetic, and near-wall shear stress around the colonized panels. The research results show that, after 12-month immersion, the mean thickness of the biofouling layer on rough and control panels reached 6.39 mm and 5.91 mm, respectively. Rough panels exhibited consistently higher RC and σ than controls, and these two parameters are strongly linearly correlated (R2=0.891). Numerical simulations reveal that increased RC enlarges the oyster settlement shear-stress window (OSSW), indicating more favorable hydrodynamic conditions for oyster settlement and growth on rough panels. Nevertheless, the hydrodynamic differences between the initial rough panels and control panels gradually diminish over time, suggesting that biological growth can progressively naturalize initially smooth substrates. These findings advance the mechanistic understanding of how small-scale roughness and biofouling co-evolve to shape oyster habitat quality and provide a quantitative basis for the eco-engineering design of artificial oyster reefs.

Climate change intensifies carbon emissions from the Earth's Third Pole: Projected trajectories of soil and ecosystem respiration - Tongqing Shen; Zhongbo Yu; Qin Ju; Junliang Jin; Guoqing Wang; Yanli Liu; Chunming Hu; Shixuan Lyu; Hui Lin; Xinrong Si; Feng Yan (Global and Planetary Change, 2026)

Silencing CD24 Inhibits Proliferation, Migration, and Chemoresistance in Triple-Negative Breast Cancer Cells - Yanli Liu; Yuhan Guo; Chien-Yu Lin; Yuanyuan Zhang; Guangfu Li; Kun Cheng (Pharmaceutical Research, 2026)

Chicken sternum cartilage protein-chelated calcium: enhance bone density in vivo and in vitro, with insights into chelation mechanism - Shikun Suo; Yanli Wang; Lihui Du; Maolin Tu; Kuo Dang; Jingyi Chen; Yi Lin; Yali Dang; Qingqing Li (Food Research International, 2026)

Adiponectin Signaling Ameliorates Cognitive Dysfunction in Type 2 Diabetic Mice by Activating the Hippocampal AdipoR2-PPARα/CREB Pathway - Hongyan Gong; Yanli Liu; Liu Xia; Bochao Niu; Jian Kong; Bin Wang; Xu Lin; Lin Lin; Yanlin Bi (Molecular Neurobiology, 2026)

The flavor properties of Amadori rearrangement products and their potentials in flavor replication of plant-based meat analogs: a review - Huan Zhan; Wenjing Xin; Yang Deng; Tao Lin; Qingshan Shen; Khizar Hayat; Yanli Ma; Yuduan Diao (Critical Reviews in Food Science and Nutrition, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Experimental investigation on the frequency characteristics of freak waves over a submerged breakwater by Variational Mode Decomposition - Yanli He; Suijun Wang; Jinbo Lin; Hongzhou Chen; Guohai Dong (Ocean Engineering, 2025)

Molecular mechanisms of dsRNA uptake and intracellular trafficking in the fat body of Locusta migratoria - Lin Yang; Yanli Wang; Shuai Li; Mureed Abbas; Zhangwu Zhao; Xuekai Shi; Kun Yan Zhu; Jianzhen Zhang (Insect Biochemistry and Molecular Biology, 2025)

Nano-sized heterogeneous photocatalyst Fe3O4@V/TiO2-catalyzed synthesis and antimycobacterial evaluation of 2-substituted benzimidazoles - Lijian Bao; Xiaodong Chen; Yanli Li; Guangyuan Zhu; Jingjun Wang; Mingyue Chen; Xingyu Bian; Qiang Gu; Yumin Zhang; Feng Lin (Molecular Diversity, 2025)

Buckwheat 2.0: From climate-resilient crop to personalized nutrition product– a model approach for future food industry - Ruikang Lin; Luman Sang; Yiqing Zhu; Yanli Wang; Xinlin Liu; Liangxing Zhao; Qun Shen; Yong Xue; Qingyu Zhao (Trends in Food Science & Technology, 2025)

Numerical study of wave heights impact on the extreme wave attenuation characteristics of plants - Jinbo Lin; Runzhen Wu; Yanli He; Hui Yang; Yang Liu; Hongfei Mao; Guanglin Wu (Ocean Engineering, 2025)

An Introduction to the Synthesis Community Integrated Model Version 2 (SYCIM2.0) and Its Simulation of the East Asian Summer Monsoon - Wenjun Liang; Wenjie Dong; Danya Xu; Bin Wang; Li Liu; Yanli Tang; Jie Yang; Song Wang; Fuhai Dao; Duofan Zheng; Chenhao Li; Fei Liu; et al. (Advances in Atmospheric Sciences, 2025)

TPM3–NTRK1 fusion confers resistance to osimertinib in lung adenocarcinoma: a model in a continuous cell line - Fang Cao; Jiayin Dai; Kun Dong; Zhenli Yang; Yanli Zhu; Changsong Qi; Dongmei Lin; Xiaocui Bian; Yuqin Liu (Human Cell, 2025)

Effects of organic selenium on metabolic responses and disease resistance in rose plants - Yanli Bian; Xiangyang Li; Deliang Gao; Guofu Zhang; Aijuan Zhang; Yizhi Feng; Zhiwei Hua; Lin Liang (Journal of Hazardous Materials, 2025)

Microbiome dynamics and metabolic regulation in rumen fibre degradation: Insights into lignocellulose breakdown and rumen fermentation strategies - Xin Wang; Yufan Lin; Ruhui Wang; Mengyao Sun; Yuan Wang; Yanli Lin; Fuyu Yang; Kuikui Ni (Chemical Engineering Journal, 2025)

Enhanced phase-transfer kinetics achieved by atomic iron catalysts on hard carbon toward low-temperature sodium-ion batteries - Xinyi Qian; Ziling Wu; Jianan Gu; Yanli Wang; Xiaomin Cheng; Jing Zhang; Hongzhen Lin; Jian Wang; Liang Zhan; Yongzheng Zhang (Chemical Engineering Journal, 2025)

Stability and Adaptability of Sugar Beet Examined Based on AMMI and BLUP–GGE Biplot Analyses - Yuhang Lin; Xinwang Dang; Xiaohang Hu; Yanli Li; Shuo Liu (Sugar Tech, 2025)

Experimental Study of the Hydrodynamic Forces of Pontoon Raft Aquaculture Facilities Around a Wind Farm Monopile Under Wave Conditions - Deming Chen; Mingchen Lin; Jinxin Zhou; Yanli Tang; Fenfang Zhao; Xinxin Wang; Mengjie Yu; Qiao Li; Daisuke Kitazawa (Journal of Marine Science and Engineering, 2025)
The integrated development of offshore wind power and marine aquaculture represents a promising approach to the sustainable utilization of ocean resources. The present study investigated the hydrodynamic response of an innovative combination of a wind farm monopile and pontoon raft aquaculture facilities (PRAFs). Physical water tank experiments were conducted on PRAFs deployed around a wind farm monopile using the following configurations: single- and three-row arrangements of PRAFs with and without a monopile. The interaction between the aquaculture structure and the wind farm monopile was examined, with a particular focus on the mooring line tensions and bridle line tensions under different wave conditions. Utilizing the wind farm monopile foundation as an anchor, the mooring line tension was reduced significantly by 16–66% in the single-row PRAF. The multi-row PRAF arrangement experienced lower mooring line tension in comparison with the single-row PRAF arrangement, with the highest reduction of 73%. However, for the bridle line tension, the upstream component was enhanced, while the downstream one was weakened with a monopile, and they both decreased in the multi-row arrangement. Finally, we developed numerical models based on flume tank tests that examined the interactions between the monopile and PRAFs, including configurations of a single monopile, along with single- and three-row arrangements of PRAFs. The numerical simulation results confirmed that the monopile had a dampening effect on the wave propagation of 5% to 20%, and the impact of the pontoons on the monopile was negligible, implying that the integration of aquaculture facilities around wind farm infrastructure may not significantly alter the hydrodynamic loads experienced by the monopile.

Developing a digital twin for dam safety management - Shao-Lin Ding; Jia-Jun Pan; Yanli Wang; Han Xu; Dian-Qing Li; Xin Liu (Computers and Geotechnics, 2025)

Progressive-composition-transformation-induced enhanced hyperthermia-based nanozyme towards long-lasting and complete therapy of cancer - Wenlong Zhang; Di Sun; Bin Yang; Jiaqi Liu; Yilin Yuan; Dezhuang Li; Yuliang Sun; Guoqiang Guan; Yanli Liu; Dapeng Wu; Hong Liao; Juntang Lin; et al. (Chemical Engineering Journal, 2025)

The dominance of K-strategy microbes enhances the potential of soil carbon decomposition under long-term warming - Yanli Gao; Jiacong Zhou; Teng-chiu Lin; Yiqing Li; Quanxin Zeng; Shidong Chen; Decheng Xiong; Qiufang Zhang; Zhijie Yang; Yusheng Yang (Applied Soil Ecology, 2025)

Enhancing exergy and economical performance of a waste heat power generation system: Multi-objective optimization and comparative analysis - Zhonglan Hou; Ismail Imechoui; Perk Lin Chong; Pengyan Guo; Yanli Deng; Yuguo Gao (Journal of Cleaner Production, 2024)

Game changer for anaerobic fermentation of paper mulberry: Sucrose-loaded biochar enhancing microbial communities and lactic acid fermentation - Jingwen Cao; Hongzhang Zhou; Xuekai Wang; Yang Wang; Yu Li; Stephen Joseph; Xiaorong Wang; Mengyao Sun; Keyi Zhang; Yanli Lin; Gang Xu; Kuikui Ni; et al. (Bioresource Technology, 2024)

Exploring Multivalency in the Development of Anti-PD-L1 Peptides for Cancer Immunotherapy - Umar-Farouk Mamani; Mohammed Nurudeen Ibrahim; Yanli Liu; John Fetse; Chien-Yu Lin; Sashi Kandel; Maryam Nakhjiri; Sushil Koirala; Yuhan Guo; Mohammed Alahmari; Kun Cheng (Pharmaceutical Research, 2024)

Study on the influence of submergence depth on the hydrodynamic and wave load characteristics of semi-submersible structures induced by a solitary wave - Jinbo Lin; Runzhen Wu; Yanli He; Yingchao Ma; Zhongbing Zhou; Yang Liu; Hongfei Mao; Guanglin Wu (Frontiers in Marine Science, 2024)
The submergence depth directly affects the safety of semi-submersible marine structures due to that the submergence depth significantly impacts on the hydrodynamic characteristics and wave loads of structures excited by extreme wave. This paper studies the influence of submergence depth on the hydrodynamic and wave load characteristics of semi-submersible structures by establishing a numerical model of the interaction between solitary waves and semi-submersible structures based on the SPH model and Rayleigh theory. Furthermore, equations for transmission coefficient, reflection coefficient, and wave load are fitted. The calculated wave heights of solitary wave propagation test case are in good agreement with the theoretical values. The maximum relative error of the wave peak is 8.4%. The calculated wave loads of submerged horizontal plates test case has a consistent trend with the experimental data. The maximum relative error of wave load peak and valley is 54% (absolute error 0.37 N). Furthermore, the interaction between solitary waves and structures with different submergence depths is investigated by using the meshless numerical model. It is found that the reflection coefficient first increases and then decreases with increasing submergence depth, and reaching a maximum value of 0.39 at the submergence depth equal to 0.0 m. On the contrary, the transmission coefficient decreases first and then increases with the increase of submergence depth. The minimum value of transmission coefficient is 0.36 with the submergence depth of 0.3 m. As the submergence depth increased, the horizontal wave load peak of the structure gradually increases, and the maximum value of 0.13 is obtained at the submergence depth of 0.7 m. The peak of vertical wave load rapidly increases with the increase of submergence depth and then gradually decreases while the trough gradually decreases with increasing submergence depth.

Intelligent conductive gels for advanced flexible electronics - Wei Wang; Hongxin Lin; Yanli Huang; Xianzeng Zhang; Zhen Yang; Wei Huang (Chemical Engineering Journal, 2024)

Homeostatic nanomedicine: Protein S-nitrosylation dyshomeostasis dominated oncotherapy based on a tumor-microenvironment-activated nanoparticle - Xiaowen Cai; Junming Li; Ruoqi Zhang; Jie Zhou; Hongmiao Lin; Xiaohua Huang; Chuanshan Xu; Yanli Li; Teng Gong (Chemical Engineering Journal, 2024)

Laboratory study of energy transformation characteristics in breaking wave groups - Guanglin Wu; Yanli He; Yizhe Zhang; Jinbo Lin; Hongfei Mao (Frontiers in Marine Science, 2024)
The spilling-breaking waves that appear in chirped wave packets are studied in a two-dimensional wave channel. These waves are produced by superposing waves with gradually decreasing frequencies. The analysis focuses on the nonlinear characteristics, energy variation, and energy transformation during the evolution and breaking of wave groups. Ensemble empirical mode decomposition is used to analyze the non-breaking and breaking energy variations of the intrinsic mode functions (IMFs). It is found that the third-order IMF component is a source of non-breaking energy dissipation and the second-order IMF, which represents a short wave group with a relatively higher energy content, is a primary source of the energy loss caused by wave breaking. Additionally, the findings reveal that among the three waves preceding the maximum crest, the wave closest to the maximum crest carried most of the energy. When wave breaking occurs, the energy dissipation caused by the wave breaking primarily originates from that wave. After wave breaking, whether it is the first breaker or subsequent breakers, the main energy dissipation occurs in a frequency range higher than the dominant frequency. This energy loss plays a significant role in increasing the energy of free waves. Moreover, a potential link between the number of carrier waves and wave breaking phenomena has been found. As the number of carrier waves increased, both the nonbreaking and breaking energy dissipation rates exhibited an overall increasing trend. The amount of nonbreaking energy dissipation was generally more than twice the breaking energy dissipation rate. For wave groups with more carrier waves, the modulation instability plays a significant role in generating larger waves. Furthermore, an analysis of the dominant frequency variations of the wave group before wave breaking suggests that wave breaking is not a sufficient condition for a frequency downshift in the wave spectra.

VfLRR-RLK1 benefiting resistance to Fusarium oxysporum reveals infection and defense mechanisms in tung tree - Haibo Wu; Wanzhen Mo; Yanli Li; Lin Zhang; Yunpeng Cao (Physiology and Molecular Biology of Plants, 2024)

Bioactive metabolite profiles and quality of Rosa rugosa during its growing and flower-drying process - Yanli Bian; Jinju Pan; Deliang Gao; Yizhi Feng; Bingjie Zhang; Le Song; Lei Wang; Xingang Ma; Lin Liang (Food Chemistry, 2024)

Reduction of haemoglobin is related to metal mixtures exposure in Chinese preschoolers: Joint effect models - Ye Fu; Minghui He; Yang Liu; Mingzhu Li; Meiqin Zhu; Yan Wang; Wei Lin; Lili Yu; Liting Yang; Yao Zhang; Yanli Liu; Hongxian Ji; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Insights into the phage community structure and potential function in silage fermentation - Yuan Wang; Yu Gao; Xin Wang; Yanli Lin; Gang Xu; Fuyu Yang; Kuikui Ni (Journal of Environmental Management, 2024)

Effective Detection of Cu(II) Ions Based on Carbon Dots@Exfoliated Layered Double Hydroxides Composites Fluorescence Probe - Quliang Lu; Yixian Mei; Yuting Wu; Houjun Lin; YanLi Li (Journal of Fluorescence, 2024)

Verification of solitary wave numerical simulation and case study on interaction between solitary wave and semi-submerged structures based on SPH model - Jinbo Lin; Lili Hu; Yanli He; Hongfei Mao; Guanglin Wu; Zhenglin Tian; Dandan Zhang (Frontiers in Marine Science, 2023)
Due to significant influence on the safety of marine structures, the interaction between extreme waves and structures is a crucial area of study in marine science. This paper focus on the verification of a solitary wave meshless SPH model and the application of the model on the interaction between solitary waves and semi-submersible structures. A solitary wave propagation model is established based on the SPH method combined with Rayleigh solitary wave theory, quintic kernel function, artificial viscosity, and Symplectic Method. The accuracy of the model is validated by comparing the calculated wave height with the theoretical value. The calculated results with relative particle spacing H 0 / d 0 ≥ 20 are in good agreement with the analytical solution. The simulated solitary wave is also quite stable with a maximum L 2 error 0.016. Therefore, the proposed SPH model can accurately simulate the propagation of the solitary waves. A case study on the interaction between solitary waves and semi-submersible platforms is conducted. The results show that the interaction between solitary waves and semi-submersible causes two double peaks with wave heights of 0.398 m and 0.410 m, respectively, induced by overtopping at the center of the platform. The wave transmission coefficient K t is 0.880 due to that the solitary wave height reduces from 0.498 m to 0.438 m after the solitary wave propagates through the semi-submersible structure. In addition, the solitary wave induces significant vertical wave loads of the structure with a load amplitude of 0.688, while horizontal wave loads are relatively small with a load amplitude of 0.089. The solitary wave arrived the structure induces the upstream and downstream overtopping and forms a hydraulic jump leading to the complex flow field. The maximum velocity at the top and bottom of the structure is 2.2 m/s and 0.8 m/s respectively. Positive or negative vortex are formed at the bottom of the leading edge, top and downstream of the structure with the maximum intensity 28 s -1 and -40 s -1 . In a word, the meshless SPH model can conveniently and accurately simulate the propagation of the solitary waves, and be applied to the investigation of the wave height, velocity, vorticity, wave load, and wave breaking of the interaction between solitary waves and structures in ocean engineering.

Thermal bleaching in the northern South China Sea: impact of abnormal environment and climate on high-latitude coral reefs - Xin Wang; Yinqiang Li; Mingqing Lin; Zhiwei Che; Weihua Mo; Yanli Chen; Shaohua Mo; Wentao Niu; Haolang Zhou (Environmental Science and Pollution Research, 2023)

Carbon capture, circular utilization, and sequestration (CCCUS): A multifunctional technology coupling underground biomethanation with geothermal energy production - Lin Wu; Zhengmeng Hou; Yachen Xie; Zhifeng Luo; Liangchao Huang; Xuning Wu; Jiashun Luo; Yanli Fang; Qianjun Chen; Wei Sun; Christian Truitt Lüddeke; Lei Yang (Journal of Cleaner Production, 2023)

Historical and projected evolutions of glaciers in response to climate change in High Mountain Asia - Lin Yang; Guangju Zhao; Xingmin Mu; Yanli Liu; Peng Tian; Puqiong; Danzengbandian (Environmental Research, 2023)

Soil organic nitrogen content and composition in different wetland habitat types along the south-east coast of China - Xiao Lin; Yanli Yang; Ping Yang; Yan Hong; Linhai Zhang; Chuan Tong; Derrick Y.F. Lai; Yongxin Lin; Lishan Tan; Yalan Tian; Kam W. Tang (CATENA, 2023)

Preparation, characterization, and evaluation of the antitumor effect of kaempferol nanosuspensions - Wen He; Junfeng Zhang; Jiale Ju; Yinghua Wu; Yuxi Zhang; Lin Zhan; Chenchen Li; Yanli Wang (Drug Delivery and Translational Research, 2023)

Conditioned medium of human menstrual blood-derived endometrial stem cells protects against cell inflammation and apoptosis of Npc1KO N2a cells - Minlin Yang; Yanchun Zhao; Xiaoying Li; Han Li; Fangfang Cheng; Yanli Liu; Zisen Jia; Ya’nan He; Juntang Lin; Lihong Guan (Metabolic Brain Disease, 2023)

Identification and protective role of CD34+ stromal cells/telocytes in experimental autoimmune encephalomyelitis (EAE) mouse spleen - Ganesh Dama; Xiaoxi Hu; Yushan Yan; Yonghai Li; Han Li; Fen Yang; Yanli Liu; Juntang Lin (Histochemistry and Cell Biology, 2023)

Assessment of future eco-hydrological regime and uncertainty under climate changes over an alpine region - Lin Wang; Jianyun Zhang; Zhangkang Shu; Zhenxin Bao; Junliang Jin; Cuishan Liu; Ruimin He; Yanli Liu; Guoqing Wang (Journal of Hydrology, 2023)

circTAB2 inhibits lung cancer proliferation, migration and invasion by sponging miR-3142 to upregulate GLIS2 - Weiling Man; Yumeng Cui; Jie Li; Yanghua Li; Jie Jin; Yang Jin; Xiaojie Wu; Rongbin Zhong; Xiang Li; He Yao; Yanli Lin; Lihe Jiang; et al. (Apoptosis, 2023)

An experimental study on nonlinear wave dynamics for freak waves over an uneven bottom - Yanli He; Guanglin Wu; Hongfei Mao; Hongzhou Chen; Jinbo Lin; Guohai Dong (Frontiers in Marine Science, 2023)
The effect of the non-uniform bathymetry on the nonlinear wave dynamics for the freak wave is investigated experimentally, with emphasis on the interrelations between different nonlinear behaviors resulting from various geometric parameters and spectral analysis. Both the frequency modulation and the nonlinear phase coupling can be provoked by the decreasing water depth and weakened after the top peak of the bar, the nonlinear exhibition for transferring energy to high-frequency contents over shoal supports that frequency modulation can reflect nonlinear phase coupling well. The consistent change of the Hilbert energy spectrum and the bicoherence shows that the main nonlinear interaction in the process of wave propagation in shallowing water is quadratic nonlinearity. In addition, the geometric study is conducted to investigate the effect of the water depth on the parametric variations, the research results show that the mean asymmetry and kurtosis change abruptly when the wave approaches the top peak of the bar. As the wave propagates along the water flume, freak waves can be generated at various locations, however, they appear more frequently as waves propagate close to the shallowest water depth, and the maximum probability of occurrence for a freak wave can be up to about 1%.

Effects of habitat usage on hypoxia avoidance behavior and exposure in reef-dependent marine coastal species - Haolin Yu; Guangjie Fang; Kenneth A. Rose; Jiazheng Lin; Jie Feng; Haiyan Wang; Qingxian Cao; Yanli Tang; Tao Zhang (Frontiers in Marine Science, 2023)
Reef habitat in coastal ecosystems is increasingly being augmented with artificial reefs (ARs) and is simultaneously experiencing increasing hypoxia due to eutrophication and climate change. Relatively little is known about the effects of hypoxia on organisms that use complex habitat arrangements and how the presence of highly preferred AR habitat can affect the exposure of organisms to low dissolved oxygen (DO). We performed two laboratory experiments that used video recording of behavioral movement to explore 1) habitat usage and staying duration of individuals continuously exposed to 3, 5, and 7 mg/L dissolved oxygen (DO) in a complex of multiple preferred and avoided habitat types, and 2) the impact of ARs on exposure to different DO concentrations under a series of two-way replicated choice experiments with or without AR placement on the low-oxygen side. Six common reef-dependent species found in the northeastern sea areas of China were used (i.e., rockfish Sebastes schlegelii and Hexagrammos otakii , filefish Thamnaconus modestus , flatfish Pseudopleuronectes yokohamae , sea cucumber Stichopus japonicus , and crab Charybdis japonica ). Results showed that lower DO levels decreased the usage of preferred habitats of the sea cucumber and the habitat-generalist filefish but increased the habitat affinity to preferred habitat types for the two habitat-specific rockfishes. Low DO had no effect on the crab’s habitat usage. In the choice experiment, all three fish species avoided 1 mg/L, and the rockfish S. schlegelii continued to avoid the lower DO when given choices involving pairs of 3, 5, and 7 mg/L, while H. otakii and the flatfish showed less avoidance. The availability of ARs affected exposure to low DO for the habitat-preferring rockfishes but was not significant for the flatfish. This study provides information for assessing the ecological effects and potential for adaptation through behavioral movement for key reef-dependent species under the increasing overlap of ARs and hypoxia anticipated in the future.

Manganese alleviates heat stress of primary cultured chick embryonic myocardial cells via enhancing manganese superoxide dismutase expression and attenuating heat shock response - Shizhen Qin; Liang Huang; Lin Lu; Liyang Zhang; Yanli Guo; Lin Xi; Xiudong Liao; Xugang Luo (Journal of Thermal Biology, 2023)

Residue behaviors, processing factors and transfer rates of pesticides and metabolites in rose from cultivation to consumption - Yanli Bian; Yizhi Feng; Aijuan Zhang; Xiaoxue Qi; Xingang Ma; Jinju Pan; Jifeng Han; Lin Liang (Journal of Hazardous Materials, 2023)

Effects of mercapto-palygorskite application on cadmium accumulation of soil aggregates at different depths in Cd-contaminated alkaline farmland - Yu Zhang; Yanli Li; Yingming Xu; Qingqing Huang; Guohong Sun; Xu Qin; Lin Wang (Environmental Research, 2023)

Alleviating the self-discharge and enhancing the polysulphides conversion kinetics with LaCO3OH nanocrystals decorated hierarchical porous carbon - Yuhang Lin; Weiqiang Tang; Siyu Wu; Yongzheng Zhang; Zhenkai Kong; Chunyin Shen; Yanli Wang; Liang Zhan; Licheng Ling (Chemical Engineering Journal, 2023)

Serum Neurofilament Light: a Potential Diagnostic and Prognostic Biomarker in Obstetric Posterior Reversible Encephalopathy Syndrome - Xiaobo Fang; Yanling Liang; Weixi Zhang; Qiong Wang; Jingsi Chen; Jia Chen; Yongqiang Lin; Yanli Chen; Li Yu; Haibin Wang; Dunjin Chen (Molecular Neurobiology, 2021)

ERP evidence for asymmetric orthographic transfer between traditional and simplified Chinese - Jiushu Xie; Yanli Huang; Ke Chen; Qian Lin; John X. Zhang; Lei Mo (Experimental Brain Research, 2021)

Preliminary study on relationships among nutritional risk, serum prealbumin, and peripheral blood T cell subsets in patients with severe COVID-19 - Yanli Li; Yanbo Sun; Jing He; Peng Zhao; Pengju Luo; Jinsong Bai; Weiming Li; Shumin Li; Yueying Lin; Yunyun Cen (Infectious Diseases, 2021)

Clinico-Psychosocial Factors Predicting Hepatocellular Carcinoma Related Knowledge Among Patients with Chronic Liver Disease - Jingyi Dai; Jun Zhao; Yingrong Du; Lin Zhuang; Yanli Ma; Virasakdi Chongsuvivatwong (Journal of Cancer Education, 2020)

FGOALS-g3 Model Datasets for CMIP6 Flux-Anomaly-Forced Model Intercomparison Project - Yaqi Wang; Zipeng Yu; Pengfei Lin; Hailong Liu; Jiangbo Jin; Lijuan Li; Yanli Tang; Li Dong; Kangjun Chen; Yiwen Li; Qian Yang; Mengrong Ding; et al. (Advances in Atmospheric Sciences, 2020)
The Flux-Anomaly-Forced Model Intercomparison Project (FAFMIP) is an endorsed Model Intercomparison Project in phase 6 of the Coupled Model Intercomparison Project (CMIP6). The goal of FAFMIP is to investigate the spread in the atmosphere-ocean general circulation model projections of ocean climate change forced by increased CO 2 , including the uncertainties in the simulations of ocean heat uptake, global mean sea level rise due to ocean thermal expansion and dynamic sea level change due to ocean circulation and density changes. The FAFMIP experiments have already been conducted with the Flexible Global Ocean-Atmosphere-Land System Model, gridpoint version 3.0 (FGOALS-g3). The model datasets have been submitted to the Earth System Grid Federation (ESGF) node. Here, the details of the experiments, the output variables and some baseline results are presented. Compared with the preliminary results of other models, the evolutions of global mean variables can be reproduced well by FGOALS-g3. The simulations of spatial patterns are also consistent with those of other models in most regions except the North Atlantic and the Southern Ocean, indicating large uncertainties in the regional sea level projections of these two regions.

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

The m6A methyltransferase METTL3 cooperates with demethylase ALKBH5 to regulate osteogenic differentiation through NF-κB signaling - Jinjin Yu; Lujun Shen; Yanli Liu; Hong Ming; Xinxing Zhu; Maoping Chu; Juntang Lin (Molecular and Cellular Biochemistry, 2020)

The T cell activating properties and antitumour activity of Staphylococcal Enterotoxin-like Q - Yanan He; Yuliang Sun; Yakun Ren; Liang Qiao; Rui Guo; Jiang Du; Xinxing Zhu; Yanli Liu; Juntang Lin (Medical Microbiology and Immunology, 2019)

Scenario analysis of ETS revenue allocation mechanism of China: based on a dynamic CGE model - Hao Li; Yuhuan Zhao; Song Wang; Jiang Lin; Ye Cao; Qiaoling Shi; Ya Liu; Yanli Xiao; Junjie Li (Environmental Science and Pollution Research, 2019)

Priming effect of litter mineralization: the role of root exudate depends on its interactions with litter quality and soil condition - Kai Tian; Xiangshi Kong; Liuhuan Yuan; Hong Lin; Zaihua He; Bei Yao; Yanli Ji; Junbo Yang; Shucun Sun; Xingjun Tian (Plant and Soil, 2019)

The dominant role of the atmospheric component of coupled models in ENSO amplitude simulations - Yanli Tang; Lijuan Li; Bin Wang; Pengfei Lin; Lin Chen; Feng Xie; Wenjie Dong; Kun Xia (Climate Dynamics, 2019)

Local root status: a neglected bio-factor that regulates the home-field advantage of leaf litter decomposition - Kai Tian; Xiangshi Kong; Jianguo Gao; Yanyan Jia; Hong Lin; Zaihua He; Yanli Ji; Zhanlin Bei; Xingjun Tian (Plant and Soil, 2018)

Knockout of CTNNB1 by CRISPR-Cas9 technology inhibits cell proliferation through the Wnt/β-catenin signaling pathway - Lihong Guan; Shaoyi Zhu; Yawei Han; Ciqing Yang; Yanli Liu; Liang Qiao; Xiaoying Li; Han Li; Juntang Lin (Biotechnology Letters, 2018)

An Optimal Dietary Zinc Level of Brown-Egg Laying Hens Fed a Corn–Soybean Meal Diet - Shizhen Qin; Lin Lu; Xichun Zhang; Xiudong Liao; Liyang Zhang; Yanli Guo; Xugang Luo (Biological Trace Element Research, 2017)

Major mutation events in structural genes of peste des petits ruminants virus through serial passages in vitro - Xiaodong Wu; Fuxiao Liu; Lin Li; Yanli Zou; Shan Liu; Zhiliang Wang (Virus Genes, 2016)

Wheat mitogen-activated protein kinase gene TaMPK4 improves plant tolerance to multiple stresses through modifying root growth, ROS metabolism, and nutrient acquisitions - Lin Hao; Yanli Wen; Yuanyuan Zhao; Wenjing Lu; Kai Xiao (Plant Cell Reports, 2015)

Association Between a Variant in ADAMTS5 and the Susceptibility to Hepatocellular Carcinoma in a Chinese Han Population - Chongyi Li; Yanli Xiong; Zhaoyang Zhong; Shiheng Zhang; Yu Peng; Lin’ang Wang; Nan Dai; Mengxia Li; Tao Ren; Lixia Gan; Dong Wang (Cell Biochemistry and Biophysics, 2015)

Altered splenic miRNA expression profile in H1N1 swine influenza - Liangzong Huang; Jun Ma; Yankuo Sun; Yanli Lv; Wen Lin; Mingjie Liu; Changsong Tu; Pei Zhou; Wanjun Gu; Shuo Su; Guihong Zhang (Archives of Virology, 2015)

Identification and expression of the elongator protein 2 (Ajelp2) gene, a novel regeneration-related gene from the sea cucumber Apostichopus japonicus - Yanli Mei; Feng Yao; Yang Wu; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

The development of transgenic mice for the expression of large amounts of human lysozyme in milk - Xiaojie Wu; Yanli Lin; Yongyi Xi; Zhenlu Shao; Yanrong Zhou; Fang Liu; Hongxing Chen (Biotechnology Letters, 2014)

Cloning and expression analysis of the gene encoding fibrinogen-like protein A, a novel regeneration-related protein from Apostichopus japonicus - Yang Wu; Feng Yao; Yanli Mei; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

The high-level accumulation of n-3 polyunsaturated fatty acids in transgenic pigs harboring the n-3 fatty acid desaturase gene from Caenorhabditis briggsae - Yanrong Zhou; Yanli Lin; Xiaojie Wu; Chong Feng; Chuan Long; Fuyin Xiong; Ning Wang; Dengke Pan; Hongxing Chen (Transgenic Research, 2014)

Aberrant methylation and loss expression of RKIP is associated with tumor progression and poor prognosis in gastric cardia adenocarcinoma - Wei Guo; Zhiming Dong; Yanli Guo; Xinwen Lin; Zhifeng Chen; Gang Kuang; Zhibin Yang (Clinical & Experimental Metastasis, 2013)

The extremely high level expression of human serum albumin in the milk of transgenic mice - Xiaojie Wu; Yanli Lin; Fuyin Xiong; Yanrong Zhou; Fang Yu; Jixian Deng; Peitang Huang; Hongxing Chen (Transgenic Research, 2012)

Plk1-mediated phosphorylation of UAP56 regulates the stability of UAP56 - Fuyin Xiong; Yanli Lin; Zhengbin Han; Gengshou Shi; Liyuan Tian; Xiaojie Wu; Qiangcheng Zeng; Yanrong Zhou; Jixian Deng; Hongxing Chen (Molecular Biology Reports, 2012)